The Role of Family and Media Environment on Aggressive Behaviour in Bulgarian Schools - Yolanda Zografova; Ekaterina Evtimova Dimitrova (Societies, 2023)
The article examines the influence of two of the main social environments on students’ aggressive behaviours. On the one hand, attention is paid to the general socio-psychological climate in the family environment and the attitude of the parents towards the child; and on the other hand, a less frequently studied aspect related to aggressive manifestations of the children and adolescents towards the parents is addressed. The study explores how watching TV shows and movies, as well as video games, in which aggression and violence predominate, is connected to the frequency and degree of manifestation of types of aggression in adolescents. The survey was conducted at the end of 2017 among 992 students in 18 primary schools, secondary schools, and vocational schools/high schools in six different cities in different regions of Bulgaria. A structured questionnaire for the study of aggression in school was designed and was intended for students. The results of the study generally show that the verbal aggression towards parents (insulting and shouting) is mostly associated with verbal aggression towards both teachers and classmates. Regarding the influence of TV shows and movies containing aggression, it was found that students who watched movies with military, fighting and bloody scenes demonstrated more frequent manifestations of verbal aggression, but the TV contents did not significantly influence the manifestations of indirect aggression and physical aggression. However, the frequency of playing video games with aggressive content has a significant effect on all investigated forms of aggression, with the strongest effect on physical aggression. Aggression in social networks is a significant factor that affects the frequency of manifestation of various forms of aggression. Students who bully others on social networks stand out as the most aggressive (verbally, physically, and indirectly).